Analysis of latex protein content by liquid chromatography coupled with tandem mass spectrometry (HPLC/MS/MS). Issue 24 (25th November 2015) - Witkowski, Bartłomiej; Szabłowska, Aneta; Malesa, Monika; Ganeczko, Monika; Biesaga, Magdalena; Kalita, Michał; Gierczak, Tomasz
Abstract : Quantification of raw latex and latex glove proteins was carried out by liquid chromatography coupled with tandem mass spectrometry. Abstract : In this work, the protein content of latex gloves and c-serum isolated from ammonia stabilized Hevea brasiliensis latex rubber concentrate was studied using a novel analytical protocol utilizing HPLC-ESI/MS/MS. Latex proteins were hydrolyzed to their corresponding building blocks and the resulting amino acid mixture was subsequently quantified by HPLC-ESI/MS/MS. Fifteen underivatized amino acids were separated with a hydrophilic interaction column (ZIC-HILIC) and the sample protein content was calculated. By utilizing a very specific and selective detection method (selected reaction monitoring mode) it was possible to minimize interferences from the sample matrix. For the natural rubber latex concentrate c-serum, the proteins were precipitated with trichloroacetic acid (TCA) and extracted with ammonia solution in water before hydrolysis. This procedure eliminated a large portion of c-serum rubber which interfered with the hydrolysis reaction. A c-serum protein concentration of 11.68 ± 0.43 mg ml −1 was obtained. The highest value available in the literature is 7.62 ± 0.28 mg ml −1 – these results prove the high efficiency of the developed analytical protocol. Data obtained for the c-serum were used to estimate the efficiency of different protein extraction methods from the latex gloves. Thus, the results obtained in this work were used to link the protein content of the raw material with the protein content of the vulcanized latex gloves for the first time. Afterwards, the optimized protocol was used to evaluate the performance of different protein removal methods, utilized during latex glove manufacturing. Thus, a practical application of the developed method is presented.